2018
DOI: 10.1111/eea.12716
|View full text |Cite
|
Sign up to set email alerts
|

Influence of larval density and dietary nutrient concentration on performance, body protein, and fat contents of black soldier fly larvae (Hermetia illucens)

Abstract: Performance and body composition of insect larvae depend on quality and quantity of their diet, and on biotic factors such as larval density. We investigated the effect of dietary nutrient concentration and larval rearing density on survival, development, growth, and protein and fat contents of larvae of the black soldier fly (BSF), Hermetia illucens L. (Diptera: Stratiomyidae). Neonate larvae were fed with a low (NC1), intermediate (NC2), or high nutrient concentration (NC3), and with four rearing densities (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
117
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(163 citation statements)
references
References 44 publications
15
117
2
3
Order By: Relevance
“…Even though all P + C‐contents tested are suitable for the complete life cycle of this species, because diet P17:C55 (P:C = 1:3; P + C = 72) supports the highest larval and adult performance and results in a high body crude protein content (42.3%) and an intermediate crude fat content (27.6%) on the diets tested, this would be the intake target for the fly feeding on chicken feed‐based diets, which matches with the P + C content of those resources that this species colonizes in the wild. Additionally, we also confirm our previous findings concerning the regulation of larval protein content within narrow limits, whereas larval crude fat content is strongly affected by nutrient concentration (Barragan‐Fonseca et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though all P + C‐contents tested are suitable for the complete life cycle of this species, because diet P17:C55 (P:C = 1:3; P + C = 72) supports the highest larval and adult performance and results in a high body crude protein content (42.3%) and an intermediate crude fat content (27.6%) on the diets tested, this would be the intake target for the fly feeding on chicken feed‐based diets, which matches with the P + C content of those resources that this species colonizes in the wild. Additionally, we also confirm our previous findings concerning the regulation of larval protein content within narrow limits, whereas larval crude fat content is strongly affected by nutrient concentration (Barragan‐Fonseca et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…This provides a functional basis for avoidance of substrates with conspecific or heterospecific larvae by gravid female S. calcitrans. The impact of larval density on fitness parameters has also been found in other Diptera including Hermetia illucens [52], B. oleae [53], D.…”
Section: Discussionmentioning
confidence: 77%
“…aegypti larvae decreased by almost 50% as larval density increased. In H. illucens, crude fat concentration is higher in larvae reared at low density than those reared at high density [52]. Other studies suggest that high larval mortality observed with increased larval density results from interference competition.…”
Section: Discussionmentioning
confidence: 95%
“…The diets were formulated by including a standard proportion of chicken feed (Opfokmeel Farmfood, Agruniek Rijnvallei Voer BV, Wageningen, The Netherlands) in the diet (63% of the total dry mass of the experimental diet, which contributed 10% protein and 31.5% carbohydrate to each treatment). This was used because it supports the full life cycle of BSF (K. Barragán-Fonseca, personal observation from BSF rearing and previous experiments (Barragan-Fonseca et al, 2018). The remaining 37% of the experimental diet was composed of the protein casein (Bio-connect, Huissen, NL), containing all the essential amino acids in high and for insects well-balanced proportions (Cohen, 2004), and the digestible carbohydrate starch (Duchefa Biochemie BV, Haarlem, NL), which served both as a nutrient and as a texturing agent.…”
Section: Experimental Designmentioning
confidence: 99%